2011
DOI: 10.1007/s11284-011-0893-5
|View full text |Cite
|
Sign up to set email alerts
|

Soil particle accumulation in termite (Macrotermes bellicosus) mounds and the implications for soil particle dynamics in a tropical savanna Ultisol

Abstract: This study investigated the influence of moundbuilding termites on soil particle dynamics on the land surface and in soil-forming processes by examining the amount of soil particles in mound structures of Macrotermes bellicosus in a highly weathered Ultisol of tropical savanna. Soil particle turnover via the mounds was estimated using particle stock data and soil turnover data from previous studies. A 4-ha study plot with six mounds of relatively uniform shape and size was investigated. Soil mass constituting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 43 publications
(50 reference statements)
1
22
0
Order By: Relevance
“…4) in spite of the large disparity in particlesize distribution (Table 1). We therefore concluded that the mound-building activity of M. bellicosus affects soil clay mineralogical composition as a result of their preferential collection of fine soil particles ( 53 m) (Abe et al 2009b(Abe et al , 2012. These findings may indicate that clay mineralogy is not linked to the ecological requirements of M. bellicosus, although our previous studies (Abe et al, 2009a(Abe et al, , 2009b suggest that soil particle selection by M. bellicosus was based on the mound structures built, which had different ecological requirements such as water-holding capacity and structural stability (Jouquet et al 2002a(Jouquet et al , 2007.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…4) in spite of the large disparity in particlesize distribution (Table 1). We therefore concluded that the mound-building activity of M. bellicosus affects soil clay mineralogical composition as a result of their preferential collection of fine soil particles ( 53 m) (Abe et al 2009b(Abe et al , 2012. These findings may indicate that clay mineralogy is not linked to the ecological requirements of M. bellicosus, although our previous studies (Abe et al, 2009a(Abe et al, , 2009b suggest that soil particle selection by M. bellicosus was based on the mound structures built, which had different ecological requirements such as water-holding capacity and structural stability (Jouquet et al 2002a(Jouquet et al , 2007.…”
Section: Discussionmentioning
confidence: 91%
“…In particular, species of the genus Macrotermes include mound-builders that construct large epigeal nests and extensive underground gallery systems and have a major influence on soil properties and functions throughout the tropics and subtropics ). Non-random mineral selection and soil-particle transport by termites during the construction and maintenance of mounds and galleries has implications for soil formation (Abe et al 2011(Abe et al , 2012. Although changes in the physical, chemical and biological characteristics of soils handled by termites have been extensively documented (Lobry de Bruyn andConacher 1990, Black andOkwakol 1997), only a limited number of researchers have addressed soil mineralogical alteration as a result of termite activity.…”
Section: Introductionmentioning
confidence: 99%
“…This plot was chosen as representative of the study area in terms of size (3.7 AE 0.4 m in height, 2.4 AE 0.2 m in basal diameter, 5.7 AE 1.5 m 3 estimated volume) and density (1.5 mounds ha À1 ) of M. bellicosus mounds (Abe et al 2012). All mounds of M. bellicosus at the study plot appeared to have reached their maximum size (based on the state of nest mutuality observed) (Abe et al 2012). Few epigeal mounds of any termite species other than M. bellicosus were observed in the plot.…”
Section: Study Plotmentioning
confidence: 99%
“…Nest body indicates the main body of the hive (including the royal chamber and baseplate) but does not include the pillars. This demarcation of the mound structures is reasonable, because soil characteristics vary considerably between the mound wall and the nest body (Abe et al 2009a(Abe et al , 2009bAbe et al 2012). The mound wall and nest body were individually weighed using a counterbalance prior to sampling.…”
Section: Field Samplingmentioning
confidence: 99%
See 1 more Smart Citation